2014
DOI: 10.3109/21681805.2014.967810
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a multiprofessional rehabilitation programme in radical cystectomy pathways: A prospective randomized controlled trial

Abstract: There was no reduction in LOS due to the preoperative and postoperative rehabilitation programme, although enhanced mobilization was achieved. The optimized minimal surgical procedure may have affected the ability to reduce LOS further with available techniques and procedures. Alternative parameters for recovery may offer more precise and relevant information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(164 citation statements)
references
References 31 publications
5
149
0
Order By: Relevance
“…Three studies did not specify the time frame of intervention implementation prior to treatment [16][17][18]. Standard care varied according to individual institutions whereby verbal or written instructions were given [15,[19][20][21], physical activity was delivered in the rehabilitation setting post-treatment [22,23], generic risk management and active mobilisation was given [18] or fast-track surgery was implemented [24]. Five studies delivered interventions in the pre-treatment period only [12,17,18,[25][26][27]; the remaining studies continued the interventions during or after treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies did not specify the time frame of intervention implementation prior to treatment [16][17][18]. Standard care varied according to individual institutions whereby verbal or written instructions were given [15,[19][20][21], physical activity was delivered in the rehabilitation setting post-treatment [22,23], generic risk management and active mobilisation was given [18] or fast-track surgery was implemented [24]. Five studies delivered interventions in the pre-treatment period only [12,17,18,[25][26][27]; the remaining studies continued the interventions during or after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The study found no significant benefits for patients in terms of length of hospital stay (p = 0.68), complication incidents (p = 0.47), severity of complications (p = 0.64), hospital readmissions (p = 0.49), mortality (p = 0.84), bowel function restoration (p > 0.05), energy intake (0.60) or protein intake (p = 0.29) [24].…”
Section: Bladder Cancermentioning
confidence: 99%
“…In one study [36], patients whose functional capacity deteriorated during PET were at higher risk of complications. There was no significant difference in complications between groups in the other studies [37,41] In one study [62], PET increased _ following pre-operative exercise training, as measured using cardiopulmonary exercise testing. All seven of these studies reported data on peak oxygen uptake, with five studies demonstrating a statistically significant improvement following pre-operative exercise training.…”
Section: Cardiorespiratory Fitnessmentioning
confidence: 86%
“…bowel resection, radical cystectomy, abdominal aortic aneurysm repair), the impact of pre-operative exercise training on peri-operative complications is less clear, with interpretation clouded by lack of standardisation in outcome measures. In the systematic review by Hijazi et al [3], three trials that included a variety of abdominal surgical populations recorded complications using the Clavien-Dindo classification, with none of them reporting significant between-group differences [36,37,41]. A recent trial of 144 patients undergoing major abdominal surgery also reported no effect of pre-operative exercise training on the severity of complications assessed using the Clavien-Dindo classification [32]; however, the proportion of patients with postoperative complications was lower (31% vs. 62%; relative risk ratio (95%CI) 0.5 (0.3-0.8)) when complications were defined as any deviation from the normal postoperative course according to the standards of the European Society of Anaesthesiology and European Society of Intensive Care Medicine [42].…”
Section: Peri-operative Clinical Outcomesmentioning
confidence: 99%
“…Pre-operative condition and risk profile is yet to be recognized in early survival care plans, and efforts should be made to inform and educate RC patients before surgery in order to reduce well-known late effects. Early nutrition care and a standardized exercise training program supervised by a multiprofessional team may lead to improved physical capacity and thereby a better basis for early ambulation and recovery [10,11]. Both the nutrition agent and physical activity are inter-related anabolic factors and involved in reducing the influence of the metabolic surgical stress response which is known to impact on early recovery and complications [12][13][14].…”
Section: Introductionmentioning
confidence: 98%